PVA/PEG - TEOS hybrid membrane for permeation of crude glycerol / Norin Zamiah Kassim Shaari - Kassim Shaari, Norin Zamiah (Institute of Graduate Studies, UiTM, 2016)
Purification of crude glycerol by employing membrane separation as a mechanism involved in the process had been widely conducted due to its environmentally process and sustainability of energy. Realizing that hybrid membrane has better thermal and mechanical stability as well as better processing flexibility as compared to membrane from pure organic polymer and inorganic material, this research investigated on the use of hybrid membrane as a barrier layer in thin film composite (TFC) for permeation of crude glycerol. In this study, thin film composite membrane consists of polysulfone as base support and hybrid membrane as the barrier layer. In a hybrid membrane formulation, a polymer blend of polyvinyl alcohol with polyethylene glycol was chosen as organic polymer which was cross-linked with tetraethylorthosilicate (TEOS). Glycerol was added as an organic additive to improve the plasticizing effect of hybrid membranes. There were three stages of work involved in the research. The first stage was investigating on base support where suitable concentration of polysulfone had been determined by water flux evaluation and investigation on suitable range of organic polymer, TEOS and glycerol concentrations. The evaluations were carried out through physical and chemical characterization and performance evaluation particularly on thin film composite through separation of crude glycerol solution. Besides good thermal and mechanical stabilities, and high surface hydrophilicity of hybrid membranes as compared to base support and membrane from pure polymer, the incorporation of glycerol had enhanced flexibility of membrane’s matrix. These properties had overcome the rigidity of structure and brittleness of ordinary hybrid membranes…